Laterally positioned flap associated with subepithelial connective tissue graft for coverage of isolated gingival recession - Thiago Marchi Martins; Alvaro Francisco Bosco; Guilherme Giovani Gazoni; Sabrina Feltrin Garcia (Revista Sul-Brasileira de Odontologia, 2012)
Introduction: The coverage of denuded roots represents one of the challenges of periodontal treatment. Among the several techniques for this purpose is the laterally positioned flap, which has undergone some modifications since its first reports and is currently combined with other techniques such as subepithelial connective tissue graft. Objective: To report a case of a 41-year-old female patient who presented Miller class I gingival recession at labial surface of tooth #43. Case report: The main symptom of the patient was dentin hypersensitivity. Clinical and radiographic exams were performed and gingival inflammation due to the presence of bacterial plaque was diagnosed as the main cause of root recession. After basic periodontal treatment, surgery for root coverage was performed. Since the area adjacent to the recession showed a good amount of attached gingiva and no interproximal bone loss, the surgical technique of choice was a laterally positioned flap associated with a subepithelial connective tissue graft. Conclusion: Postoperative assessment showed complete root coverage, an increased keratinized gingival band, absence of dentin hypersensitivity, and an excellent esthetic outcome.